Plasma Markers of Degradation of Extracellular Matrix with Intrauterine Herpes Infection - S. N. Beniova; S. Y. Figol; O. A. Kornilova (Детские инфекции (Москва))
The study of the dynamics of serum levels of matrix metalloproteinases (MMP-8, MMP-9) and tissue inhibitor (TIMP-1) in newborns with intrauterine herpes infection in the early neonatal period. It has been studied 38 children born to mothers with chronic herpes infections (НI). High concentrations of plasma matrix metalloproteinase and tissue inhibitor in infants with intrauterine herpes infection indicates the activation of the destruction of the extracellular matrix and is preceded by the implementation of the clinical manifestations of infection. Increased levels of MMP-9, while maintaining stable or decreasing values of TIMP-1 reflects the pathogenic activity of the infectious process, accompanied by excessive proteolysis.